Occurrence of Two 5-Aminolevulinate Biosynthetic Pathways in Streptomyces nodosus subsp. asukaensis Is Linked with the Production of Asukamycin - Petříček, Miroslav (American Society for Microbiology, 2006)
We report the results of cloning genes for two key biosynthetic enzymes of different 5-aminolevulinic acid (ALA) biosynthetic routes from Streptomyces. The genes encode the glutamyl-tRNA(Glu) reductase (GluTR) of the C(5) pathway and the ALA synthase (ALAS) of the Shemin pathway. While Streptomyces coelicolor A3(2) synthesizes ALA via the C(5) route, both pathways are operational in Streptomyces nodosus subsp. asukaensis, a producer of asukamycin. In this strain, the C(5) route produces ALA for tetrapyrrole biosynthesis; the ALA formed by the Shemin pathway serves as a precursor of the 2-amino-3-hydroxycyclopent-2-enone moiety (C(5)N unit), an antibiotic component. The growth of S. nodosus and S. coelicolor strains deficient in the GluTR genes (gtr) is strictly dependent on ALA or heme supplementation, whereas the defect in the ALAS-encoding gene (hemA-asuA) abolishes the asukamycin production in S. nodosus. The recombinant hemA-asuA gene was expressed in Escherichia coli and in Streptomyces, and the encoded enzyme activity was demonstrated both in vivo and in vitro. The hemA-asuA gene is situated within a putative cluster of asukamycin biosynthetic genes. This is the first report about the cloning of genes for two different ALA biosynthetic routes from a single bacterium.